Endoftalmitis Et Causa Ulkus Kornea dan Glaukoma Sekunder dengan Penyakit Mata Tiroid di Bidang Agromedicine - Rosy Osiana; Rani Himayani; Helmi Ismunandar (Medula, 2020)
Thyroid Eye Disease (TED) is a disease of the eye that is characterized by bilateral proptosis which is added by increasing levels of T3, T4 and increasing TSH levels. TED patients are common exposure to keratitis in the cornea that is not properly closed and not completely closed by the palpebra. Corneal ulcers can occur due to keratitis. TED patients can also be approved with glaucoma. 31-year-old man who came with the main complaint that refused perfect vision since 2 weeks of SMRS. The initial complaint of the patient was raised casually for the second time since 3 weeks of SMRS. The patient has a view about the use leaf extract of the right eye so that make red eye and vision decrease increasingly then left eye and enlarge white spots. In patients complaining of weight loss of 14 kg for 1 month released with weakness, nausea, sweating, and shaking compilation in resting conditions. At the time of physical examination found a general situation, the level of compost mentis awareness, blood pressure 140/100 mmhg, pulse 130 x / min. The results of physical examination on the eyes obtained sharp vision of VOD 1/300 and VOS 6/60, exoftamus (+) ODS, ciliary injection (+) OD, conjunctival injection (+) ODS, corneal edema (+) OD, cumhipopion (+ ) OD size 2 mm x 1 mm, shallow anterio OD occer camera, and ODS secret (+). Laboratory examination T3 and T4 increased and TSH decreased. Treatment involves education, antibiotik, antihistamin, kalium, beta blocker, antifungal, diuretic, and steroid.